Neuroinflammation and brain–peripheral interaction in ischemic stroke: A narrative review - Cheng, Wenjing; Zhao, Qing; Li, Chengzhen; Xu, Yunzhi (Frontiers in Immunology, 2023)
Excessive immune activation within the lesion site can be observed after stroke onset. Such neuroinflammation within the brain parenchyma represents the innate immune response, as well as the result of the additional interactions between peripheral and resident immune cells. Accumulative studies have illustrated that the pathological process of ischemic stroke is associated with resident and peripheral immunity. The infiltration of peripheral immune cells within the brain parenchyma implicitly contributes to secondary brain injuries. Therefore, better understanding of the roles of resident and peripheral immune reactions toward ischemic insult is necessary. In this review, we summarized the interaction between peripheral and resident immunity on systemic immunity and the clinical outcomes after stroke onset and also discussed various potential immunotherapeutic strategies.